The Industrial Orthopaedic Society Supports and Controls The Manor House Hospital (London : Edson (Printers) Ltd.)
1920s 2 pages THE INDUSTRIAL ORTHOPAEDIC SOCIETY (Registered as a Friendly Society, No. 1483 London) SUPPORTS AND CONTROLS THE MANOR HOUSE HOSPITAL GOLDERS GREEN, LONDON, N.W.11 YOU can join this Society if you are willing to PAY One Shilling Entrance Fee and a Contribution of ONE PENNY per week, which not only enables you TO HELP those who need your assistance, but you with OTHERS will be taking your share of responsibility IN OBTAINING control of an institution equipped for THE SPECIALISED TREATMENT so many need but which THEY COULD NOT OBTAIN owing to its high cost UNLESS YOU HELP by becoming a supporter Full particulars can be obtained by application to The Secretary, Manor House Hospital, Golders Green The First Labour Hospital 36/H24/47